Culturally Adapted Digital Mental Health and Smart Tourism Interventions for Mainland Chinese Students in Hong Kong - Rui, Liu; Guo, Xutian; Ye , Xiaofei; Yang, Guangyu (Journal of Sustainable Competitive Intelligence, 2025)
Purpose: This paper suggests a digital mental health (DMH) and smart tourism model with cultural adaptation, to assist in maintaining the psychological health and the culture adjustment of mainland Chinese students studying in Hong Kong. Its objective is to intertwine the elements of mental health with the mobility of the city, way finding technologies, and peer interaction to turn the day-to-day navigation process into a source of emotional management, learning culture, and institutional smartness. Methodology: A systematic literature review was performed based on PRISMA 2020 guidelines. Predefined keywords that were used include digital mental health, cultural adaptation, mobility, and smart tourism, which were searched in Scopus, Web of Science, PubMed, and Google Scholar. The inclusion was based on the PICOS framework and 55 studies published between 2008 and 2025 were included. Coding and reliability checks with thematic synthesis facilitated with qualitative content analysis (NVivo 14) were supplemented with data triangulation, making the methodology robust. Originality/Value: The study contributes to existing body of knowledge by incorporating DMH interventions with mobility and smart tourism technologies - which have not been combined to help students to cross-border to date. It also places the framework in the context of sustainable competitive intelligence on student mobility and engagement data as an institutional benefit. Key Results: It is demonstrated that the use of culturally adapted DMH tools leads to anxiety and depressive symptoms decreasing in students, whereas guided exploration of the city and the use of AR-guided navigation improve mobility confidence and sociocultural adaptation. Peer-social capabilities help to decrease isolation and create a sense of belonging. Collectively these elements can provide real-time institutional intelligence that can help in early detection, service planning and long term strategic competitiveness. Contributions: The study proposes an interdisciplinary model connecting the mental health, mobility, tourism technologies, and competitive intelligence. It shows the way universities may use smart-city settings to encourage well-being, cultural inclusiveness, and evidence-informed decision-making.